The Role of BMP Signaling in Endothelial Heterogeneity - Han, Orjin; Pak, Boryeong; Jin, Suk-Won (Frontiers in Cell and Developmental Biology, 2021)
Bone Morphogenetic Proteins (BMPs), which compose the largest group of the Transforming Growth Factor beta (TGF-ß) superfamily, have been implied to play a crucial role in diverse physiological processes. The most intriguing feature of BMP signaling is that it elicits heterogeneous responses from cells with equivalent identity, thus permitting highly context-dependent signaling outcomes. In endothelial cells (ECs), which are increasingly perceived as a highly heterogeneous population of cells in respect to their morphology, function, as well as molecular characteristics, BMP signaling has shown to elicit diverse and often opposite effects, illustrating the innate complexity of signaling responses. In this review, we provide a concise yet comprehensive overview of how outcomes of BMP signaling are modulated in a context-dependent manner with an emphasis on the underlying molecular mechanisms and summarize how these regulations of the BMP signaling promote endothelial heterogeneity.